Part I: Bioinspired reactions in the synthesis of complex molecules. Part II: New generation of In(III)-pybox complex in asymmetric synthesis - Zhao, Junfeng (2011)
This thesis includes two parts: Part I, bioinspired reactions in the synthesis of complex molecules; Part II, new generation of In(III)-pybox complex in asymmetric synthesis. Two efficient methodologies inspired by nature for the synthesis of complex molecules had been developed in the first part. Firstly, we reported a highly efficient epoxide opening-initiated cascade polyene cyclization in the presence of water-tolerant Lewis acid (InBr3). Latter, an intramolecular [2 + 2]-cycloaddition reaction of ene-allenone had been developed in the course of our effort toward biomimetic polyene cyclization. The mild reaction conditions, good to excellent yields, excellent diastereoselectivities, and the simplicity of the reaction procedure make these methods attractive for the synthesis of complex polycyclic natural products. In the second part of this thesis, we demonstrated that the In(Ш)-pybox complex is an efficient catalyst for bidentate substrates by using the asymmetric carbonyl-ene reaction of glyoxylate esters as the model reaction. In addition, a new generation of In(III)-pybox complexes based on the counterion effect has been developed and applied to asymmetric ketone-ene reaction of trifluoropyruvate and a more challenging Mukaiyama aldol reacton successfully. The increased catalytic efficiency will expand further application of chiral indium complex in the asymmetric synthesis.